2011
DOI: 10.1186/1476-511x-10-5
|View full text |Cite
|
Sign up to set email alerts
|

The proprotein convertase subtilisin/kexin type 9 gene E670G polymorphism and serum lipid levels in the Guangxi Bai Ku Yao and Han populations

Abstract: BackgroundProprotein convertase subtilisin-like kexin type 9 (PCSK9) plays a key role in regulating plasma low-density lipoprotein cholesterol (LDL-C) levels. However, the association of E670G (rs505151) polymorphism in the PCSK9 gene and serum lipid levels is inconsistent in several previous studies. The present study was undertaken to detect the association of PCSK9 E670G polymorphism and several environmental factors with serum lipid levels in the Guangxi Bai Ku Yao and Han populations.MethodsA total of 649… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 59 publications
2
36
1
Order By: Relevance
“…Moreover, in German [27], Brazilian [26], and Tunisian populations [28], as well as in the Belgium Stroke Study [29], the PLIC study [25], and the LCAS [30], PCSK9 E670G was associated with increased TC and/or LDL-C levels or an increased risk of atherosclerosis. In healthy UK men [15], Taiwanese [31], Guangxi Bai Ku Yao, and Han Chinese populations [32], and in the PROSPER study group [14], PCSK9 E670G was not associated with increased TC and/or LDL-C levels or increased risk of atherosclerosis.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, in German [27], Brazilian [26], and Tunisian populations [28], as well as in the Belgium Stroke Study [29], the PLIC study [25], and the LCAS [30], PCSK9 E670G was associated with increased TC and/or LDL-C levels or an increased risk of atherosclerosis. In healthy UK men [15], Taiwanese [31], Guangxi Bai Ku Yao, and Han Chinese populations [32], and in the PROSPER study group [14], PCSK9 E670G was not associated with increased TC and/or LDL-C levels or increased risk of atherosclerosis.…”
Section: Introductionmentioning
confidence: 98%
“…The effects of alcohol consumption on TC and LDL-C levels are depended upon genotypes. In their study AA genotype had lower serum TC and LDL-C levels in drinkers than in non-drinkers [19] . In our study similar type of result found that HDL-C level was much higher than LDL-C level in GG genotype than AA and AG genotype in control subject.…”
Section: Lipid Profile Analysismentioning
confidence: 81%
“…After the isolation of genomic DNA according to procedure previously described by Aung et al [19] , 1% Agarose Gel Electrophoresis (AGE) was run to check the presence of DNA in the eluted solution. The genomic DNA was seen in 1% AGE (Fig.…”
Section: Results and Discussion Genomic Dna Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…A gain-of-function mutation, Glu670Gly, has been associated with increased LDL cholesterol and coronary atherosclerosis, but not in those of Caucasian or African descent. [56][57][58][59] In the Italian population, the same variant was associated with increased intima media thickness. 60 The Asp374Tyr variant has been found in Utah, Norway, and England.…”
Section: Genetic Variants Related To Pcsk9mentioning
confidence: 92%